If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -20 = 7x + 3 Reorder the terms: -20 + 3x = 7x + 3 Reorder the terms: -20 + 3x = 3 + 7x Solving -20 + 3x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -20 + 3x + -7x = 3 + 7x + -7x Combine like terms: 3x + -7x = -4x -20 + -4x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -20 + -4x = 3 + 0 -20 + -4x = 3 Add '20' to each side of the equation. -20 + 20 + -4x = 3 + 20 Combine like terms: -20 + 20 = 0 0 + -4x = 3 + 20 -4x = 3 + 20 Combine like terms: 3 + 20 = 23 -4x = 23 Divide each side by '-4'. x = -5.75 Simplifying x = -5.75
| 6-x=-2x-8 | | 500*500=(300*300)+x^2 | | 2ln(4x)=16 | | -x=-6-2-2x-8x | | 7c-c=17-c | | x/g-43=1000 | | 16x-1=12x+1 | | 20(q-922)=840 | | 49=25+a^2 | | 6y+12=2y+y | | 9+8=c^2 | | 5(X-20)+4(X-22)=X-4 | | 5/4r-8=1/4r | | x+2+2x-6=20 | | -5n-8-7n=-15 | | 12/15x100/1 | | 2-4(1+9f)=-35 | | 8y+12=6y+y | | -3(2c-5)=29+8c | | -31=3(2k-9) | | 3(3t-2)=5t+10 | | 3(x+60)=5x | | 3(9y+7)=-15 | | 24+3y=6x | | -7(8-3b)=-20 | | x*log(x)-x=K | | E+e+2e+2e=180 | | .5x-.35x=2.5x+9.4 | | (12-3x)/2 | | 7x-2y=11fory | | px^2+(2p+6)x+16=0 | | 3(t-3)+6=3(2t-6) |